Estimating the potential impact of nonvoters on outcomes of parlimentary elections in proportional systems with the applications to German national elections from 1949 to 2005 - Ulrich Kohler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2009)
"If [voter] turnout was 100%, would it affect the election result?" (Bernhagen and Marsh 2007) is a frequently asked research question. So far, the question has been primarily answered regarding the changes in the distribution of votes. This article extends the analysis to changes in the distribution of seats and government formation. It proposes a method that factors in apportionment methods, barring clauses, size of parliaments, leverage of nonvoters, closeness of election results, and individual characteristics of nonvoters. The method is then applied to German national elections from 1949 to 2005. The application shows that Germany's Social Democratic Party (SPD) would have gained from the counterfactual participation of nonvoters, although usually not enough to result in a government change. However by the 1994 and 2005 elections evidence shows that such a government change could have happened.
Keywords: 300